2022
DOI: 10.1002/pc.26671
|View full text |Cite
|
Sign up to set email alerts
|

Physical, thermal, and mechanical properties of Al2O3/SiO2 infused jute/glass fiber resin composite materials in relation to viscosity

Abstract: Jute/glass fibers epoxy composites are significantly used in construction, automotive, aerospace, and wind turbine industries. In this work, jute/glass fibers epoxy composites reinforced with two different types of filler such as the Al2O3 and SiO2 particles at different weight rations (5, 10, and 15 gm) were investigated in relation to the viscosity. The composite samples required for various tests were fabricated in conventional hand lay‐up method. Physical, thermal stability, and mechanical properties such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This is correlated with the SiO 2 addition to pure Mg, where the resulting damping loss rate, representing the material's ability to absorb or stop vibrations, was significantly enhanced [30,33]. Silicon dioxide has potential as a vibrationabsorbent material [34] because of its visco-elastic properties, which results in higher energy dissipation as heat, hence leading to superior damping capabilities [35].…”
Section: Damping Characterizationmentioning
confidence: 96%
“…This is correlated with the SiO 2 addition to pure Mg, where the resulting damping loss rate, representing the material's ability to absorb or stop vibrations, was significantly enhanced [30,33]. Silicon dioxide has potential as a vibrationabsorbent material [34] because of its visco-elastic properties, which results in higher energy dissipation as heat, hence leading to superior damping capabilities [35].…”
Section: Damping Characterizationmentioning
confidence: 96%
“…These laminates, made up of fabrics and/or fiber mats, are mostly made of glass, due to its low cost and excellent mechanical properties [3]. Studies have reported that hybrid laminates can achieve increased tensile strength, bending strength, impact strength, compression-after-impact strength, reduced water absorption, and improved thermal stability compared to their single-component counterparts [4,5]. Hence, in plant-based hybrid laminates, glass layers can mitigate some of the detrimental characteristics of the lignocellulosic ones such as seasonality, limited mechanical properties, high water absorption, suboptimal hydrophobicity, and vulnerability to fracture that make them less desirable for certain applications (e.g., civil construction, furniture, etc.)…”
Section: Introductionmentioning
confidence: 99%